Antibacterial mechanism of Cu-bearing 430 ferritic stainless steel - Zhang, Zhuang (Rare Metals, 2021)
Copper (Cu)-bearing stainless steel has testified its effectiveness to reduce the risk of bacterial infections. However, its antibacterial mechanism is still controversial. Therefore, three 430 ferritic stainless steels with different Cu contents are selected to conduct deeper research by the way of bacterial inactivation from two aspects of material and biology. Hereinto, electrochemical and antibacterial results show that the increase in Cu content simultaneously improves the corrosion resistance and antibacterial property of 430 stainless steel. In addition, it is found that Escherichia coli (E. coli) on the surface 430 Cu-bearing stainless steel by the dry method of inoculation possesses a rapid inactivation ability. X-ray photoelectron spectroscopy (XPS) aids with ion chelation experiments prove that Cu (I) plays a more crucial role in the contact-killing efficiency than Cu (II), resulting from more production of reactive oxygen species (ROS). GRAPHICAL ABSTRACT: [Image: see text]